(NsOBRANIE SO^INENIJ W ^ETYREH TOMAH(B; s (NpOWESTI I RASSKAZY(B: [1887-1900] / s (N~ASTX (B1s - (NwERESAEW(B, (Nw(B.(Nw(B.s ((NmOSKWA(B: s (NpRAWDA(B, s, 1985)
(Nw PERWYJ TOM WO[LI POWESTI I RASSKAZY (B(1887-1900): "(NzAGADKA(B", "(NpORYW(B", "(NtOWARI]I(B", "(NbEZ DOROGI(B", "(NpOWETRIE(B", "(NlIZAR(B", "(Nk USPEHU(B", "(NwANXKA(B", (NnA \STRADE(B", "(NzAPISKI WRA^A(B", "(NpO POWODU (B"(NzAPISOK WRA^A(B".s
rus
Keywords: (NpOWESTI I RASSKAZYs